Joining three car body steel sheets by clinching method - Kaščák Ľuboš (Open Engineering, 2016)
The optimization of a car body in terms of cost can be achieved by using different materials in various positions of the car in order to utilize specific properties of each different material. Resistance spot welding is the most used method of joining in car body production, but it is not always easy or even possible to join some combination of materials by this method. Clinching is an alternative method to spot welding, as a combination of drawing and forming. The research is focused on the evaluation of clinched joints’ properties using shearing test and metallographic observation of material structure.